Integrative Review on Nutritional Dynamite for Anaemia of Adolescent Girls: Personalized Medicine : A Review - Annalakshmi, S. (Asian Journal of Pharmaceutical Research and Development, 2021)
Moringa Oleifera is a Miracle tree, native to India. This golden tree has high nutritional value in its each and every part. This locally available, economical, self growing tree has immense potential to control Iron Deficiency Anaemia. According to the “The Comprehensive National Nutrition Survey, Thematic Reports- 2019” states that investing in the nutrition of the 1.2 billion adolescents, will shape the world’s future. Ensuring Indian adolescents are nourished and growing well is critical to achieving India’s demographic dividend. Moringa is perhaps plant based, iron rich inexpensive food. Iron is notoriously difficult for the body to absorb, so it is necessary to eat foods that also include vitamins that will help our body to retain iron. If we try to prevent or drastically increase the iron level among adolescents adding Moringa to the diet can help to bring out the massive and enormous change.